ANALISIS DAMPAK KETIDAKADAAN BUOY TERHADAP BADAN METEROLOGI KLIMATOLOGI DAN GEOFISIKA (BMKG) STUDI KASUS TSUNAMI PALU - Siska Harmi; Najlah rizky widati hidayat (Riset Sains dan Teknologi Kelautan, 2023)
Tsunamis are large waves generated by earthquakes or underwater volcanic eruptions. Tsunami waves increase in height as they approach the coast, with speed related to ocean depth rather than distance. The Meteorology, Climatology and Geophysics Agency (BMKG) plays an important role in tsunami monitoring and warning in Indonesia, although some areas, such as Palu, may not have adequate buoys. This research identifies the obstacles faced by BMKG in carrying out its tsunami monitoring and warning duties, with a focus on Palu. The research method includes literature analysis through written sources such as journals, books, research reports and official documents. The results highlighted the lack of buoys, the limitations of early warning and the consequences for the community. Recommendations included improving public knowledge about tsunamis, developing disaster information technology and revisiting the use of buoys. The study illustrates the importance of land planning, infrastructure and community capacity in the face of earthquakes and tsunamis. Keywords: BMKG, Buoy, Impact, Early Warning and Palu Tsunami